The Effect of Learning Model and Motivation Level on Students’ Self-Eficacy - Hasani, Muhamad Khaeriva; K, Komarudin; Juliantine, Tite (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
Self-Efficacy is a person's belief on his ability to complete certain tasks. The purpose of this study was to determine the influence differences between two learning models, namely TPSR and Cooperative Learning on students who have high and low motivation levels to increase self-efficacy of the fifth grade students. Experimental methods with 2x2 factorial design was used. The sample of this research were105 fifth grade students at SDN 208 Luginasari, Bandung, chosen by using total sampling technique. Data analysis used SPSS version 21 with hypothesis testing through Two Way Anova. The results of the analysis and calculation of the data revealed that; there was no significant difference in the effect between the two learning models on increasing students’ self-efficacy; there was an interaction between learning models with motivation towards increasing self-efficacy; there was no significant difference in the effect between the two learning models with high levels of motivation towards the increase of self-efficacy; and there was no significant difference in the effect between the two learning models with low motivation levels on increasing self-efficacy. The conclusion of this study is that both of the learning models have the same effect on both high and low motivation levels on the student self-efficacy and there is an interaction between learning models and motivation on increasing the student self-efficacy.